Minimizing Material Handling Costs with the SLP Method and Material Transport Equipment in Steel Pipe Companies - Nur Kalim; Lukmandono (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
Factors that influence the amount of material handling costs are the distance of material movement, methods, and tools (equipment) used. The distance of material movement is strongly influenced by the layout of the production facility. The new layout design using the SLP method is expected to reduce the distance of material or product movement in PT. A B C. From the analysis results obtained the total distance of material transfer at the initial layout of the production process at PT. ABC of 1761 meters / month with material handling costs of Rp. 315,390,000.00 / month. Then an analysis of the use of material transport equipment results in the replacement of a crane with a sloping plane to connect the production machine. So the cost of material handling using the inclined plane becomes Rp. 0. The use of sloping fields can only be used on certain production machines. By using the Systematic Layout Planning (SLP) method, there are 3 alternative layouts produced. The most optimal alternative layout is alternative layout 3 with monthly material handling cost savings of Rp. 68,100,000.00 or 21% of the initial material handling layout cost.